Conversion of natural gas for coproduction of methanol-hydrogen and methanol-ammonia - G. V. Meshcheryakov; Yu. А. Komissarov (Тонкие химические технологии)
In this work the requirements are shown for conversion branches of co-productions of methanol-hydrogen and methanol-ammonia. Analysis of existing methods of natural gas conversion was carried out. Using steam conversion and combined one, consisting of steam and steam-hydrogen conversion was shown to be expedient. Analysis of pipe-still heaters and mine reactors for natural gas conversion was carried out. Designs of reactors for natural gas conversion are offered.